Hokkaido Dairy Farm Cosmopolitics of Otherness and Security on the Frontiers of Japan - Hansen, Paul (State University of New York Press, 2024)
Argues that the dairy industry in Japan has always been entwined with notions of Otherness and security seeking, notably in terms of frontiers